2019
DOI: 10.1002/14651858.cd011671.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Machine perfusion preservation versus static cold storage for deceased donor kidney transplantation

Abstract: Machine perfusion preservation versus static cold storage for deceased donor kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
204
2
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(230 citation statements)
references
References 61 publications
8
204
2
16
Order By: Relevance
“…Guidance from the Cochrane Handbook for Interventional Systematic Reviews and the PRISMA guidelines (including the PRISMA checklist) were followed for this review . The protocol for the review was published prospectively through Cochrane …”
Section: Methodsmentioning
confidence: 99%
“…Guidance from the Cochrane Handbook for Interventional Systematic Reviews and the PRISMA guidelines (including the PRISMA checklist) were followed for this review . The protocol for the review was published prospectively through Cochrane …”
Section: Methodsmentioning
confidence: 99%
“…There are several different modalities of ex vivo machine organ perfusion including hypothermic (HMP) and normothermic (EVNP) systems that have both been used in clinical transplantation. A recent Cochrane review found that HMP reduced the risk of DGF compared to static cold storage (RR 0.77, P = 0.0006), with 7.3 and 13.6 kidney perfusions needed to prevent 1 case of DGF in DCD and DBD kidneys, respectively . There were no RCTs comparing HMP and EVNP.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane review found that HMP reduced the risk of DGF compared to static cold storage (RR 0.77, P = 0.0006), with 7.3 and 13.6 kidney perfusions needed to prevent 1 case of DGF in DCD and DBD kidneys, respectively. 47 There were no RCTs comparing HMP and EVNP. However, HMP has failed to provide accurate methods of assessing organ viability or predicting DGF, 48 suggesting that EVNP may have an added advantage over HMP.…”
Section: E315mentioning
confidence: 99%
“…The whole spectrum of kidney transplant options is available in Lithuania: preemptive transplantation, living‐related and deceased donor transplantation, paired and ABO incompatible donation, desensitization of highly sensitized recipients, transplantation from a nonheart‐beating donor, and combined kidney transplantation (ie, combined with pancreas, heart or liver). For extended criteria donors, perfusion‐based machine preservation has been used since 2016 . Laparoscopic living donor nephrectomy was introduced in 2017, and the majority of living‐related donors are now managed successfully this way .…”
Section: Modern Kidney Transplantationmentioning
confidence: 99%
“…For extended criteria donors, perfusion-based machine preservation has been used since 2016. 9 Laparoscopic living donor nephrectomy was introduced in 2017, and the majority of living-related donors are now managed successfully this way. 10 Patients from abroad, mostly from the post-Soviet states, come to Lithuania for living-related kidney transplantation.…”
Section: Modern Kidney Transplantationmentioning
confidence: 99%